Complete Video-Assisted Thoracoscopic Surgery and Traditional Open Surgery for Elderly Patients With NSCLC - Mao, Yi; Gao, Zhaojia; Yin, Yajun (Frontiers in Surgery, 2022)
Objective: To observe the efficacy of complete video-assisted thoracoscopic surgery (CVATS) and traditional open surgery (TOS) in the treatment of elderly patients with non-small cell lung cancer (NSCLC) and their influence on cardiopulmonary function. Methods A total of 120 elderly patients with primary NSCLC who were treated surgically in our hospital from January 2018 to January 2021 were selected and divided into the study group and the control group according to the different surgical procedures, 60 patients in each group. CVATS was used in the observation group and TOS in the control group. The surgical indexes and cardiopulmonary function indexes were observed and compared between the two groups. The serum C-reactive protein (CRP) level and visual analog scale's (VAS) score of the patients at different time points were detected. The incidence of postoperative complications was compared between the two groups. Results The perioperative indexes such as operation time were significantly different between the two groups (p < 0.05), but the number of lymph node dissection was not significantly different (p > 0.05). The serum CRP level and VAS score of the observation group were significantly lower than those of the control group on the 1st, 3rd, and 7th postoperative days (p < 0.05). There were significant differences in cardiopulmonary function between the two groups on the 7th postoperative day (p < 0.05). The incidence of adverse reactions in the observation group was significantly lower than that in the control group (p > 0.05). Conclusion CVATS is effective in the treatment of NSCLC. Compared with TOS therapy, CVATS has less damage to cardiopulmonary function and fewer complications, which is conducive to the rehabilitation of elderly patients. It is a safe and reliable scheme for the treatment of elderly patients with NSCLC.